FORMATION OF INVESTMENT-INNOVATION STRATEGY FOR FOOD INDUSTRY ENTERPRISES IN THE CONTEXT OF DIGITALIZATION AND RISK ENVIRONMENT - NEMASHKALO, Karina; DANKO, Yuriy; RYBALKO, Serhiy; LYZOHUB, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is dedicated to the issues of forming the investment-innovation strategy for food industry enterprises in the context of digitalization and a risky environment. The aim of the article is to substantiate the investment-innovation strategy for food industry enterprises, considering the current risks and the digital transformation of the country’s economy. The article examines the investment-innovation activity of food industry enterprises and its role in ensuring their competitiveness in the face of modern economic challenges. The study analyzes existing approaches to the formation and implementation of investment-innovation strategies in enterprises and substantiates the importance of integrating investments in the development of innovative technologies to achieve sustainable economic growth. It is revealed that the investment-innovation strategy is a key tool for improving the efficiency of enterprises and adapting to changes in the global economic environment. The research identifies that the investment-innovation activity of food industry enterprises is accompanied by numerous risks that directly affect their financial stability, production efficiency, and market prospects. The main risk groups include financial (high capital intensity, limited access to financing, instability of exchange rates, low investment profitability), technological (significant costs for research and development, rapid technological obsolescence, integration difficulties), market (demand uncertainty, competition, production seasonality, raw material price fluctuations), regulatory (changes in environmental requirements and tax policy), organizational and personnel (insufficient staff qualifications, resistance to change, risk of ineffective management), and environmental (climate changes, growing waste disposal requirements). The study substantiates the investment-innovation strategy for food industry enterprises, aimed at improving production efficiency, creating value-added products, reducing costs, improving product quality, and minimizing environmental impact. It is determined that to achieve the goal, the enterprise should follow a set of principles: sustainable development, digital transformation, flexibility, adaptability, cooperation, partnership, and risk management. The proposed strategy includes a comprehensive set of measures in the following directions: technological modernization, innovative product development, environmental sustainability, financial support, staff development, and digital marketing. The implementation of the investment-innovation strategy for food industry enterprises will ensure a range of positive changes aimed at increasing the effectiveness of their operations and strengthening market positions: increasing the profitability of food enterprises, entering new markets, optimizing production processes, enhancing customer loyalty, and improving the level of innovation culture and digital literacy of staff.